Heparinase‐modified thromboelastography in cats. Issue 1 (21st December 2016) - Cuq, Benoît; Dunn, Marilyn E.; Bédard, Christian
Abstract: Background: Evaluation of underlying hemostatic function is challenging when feline patients are receiving an anticoagulant medication. Discontinuing the anticoagulant to obtain accurate results for hemostatic testing may lead to thrombotic complications. The addition of heparinase to blood samples may mitigate the effects of exogenous heparin and allow hemostatic testing. Methods: Tissue factor (TF)‐activated thromboelastography (TEG) was performed using citrated whole blood from 19 cats. Assays were performed using citrated whole blood, with and without addition of unfractionated heparin to a concentration of 0.2 U/mL. For each blood sample, TEG assays were performed using a standard cup and a heparinase‐coated cup. Key Findings: For TEG variables R, k, α‐angle, and MA, mean values were not statistically different when citrated blood was used with standard or heparinase‐coated cups. Heparinized blood assayed in standard cups displayed a significantly increased R and k, and significantly decreased α‐angle and MA when compared to heparinized blood assayed in heparinase‐coated cups. TEG variables for heparinized blood assayed in heparinase cups was not statistically different from those of the citrated whole blood without added heparin. Significance: Heparinase modified, TF‐activated, TEG reverses heparin effects in feline‐citrated blood.